2024
DOI: 10.1007/s40820-023-01299-9
|View full text |Cite
|
Sign up to set email alerts
|

A Review on Engineering Transition Metal Compound Catalysts to Accelerate the Redox Kinetics of Sulfur Cathodes for Lithium–Sulfur Batteries

Liping Chen,
Guiqiang Cao,
Yong Li
et al.

Abstract: Engineering transition metal compounds (TMCs) catalysts with excellent adsorption-catalytic ability has been one of the most effective strategies to accelerate the redox kinetics of sulfur cathodes. Herein, this review focuses on engineering TMCs catalysts by cation doping/anion doping/dual doping, bimetallic/bi-anionic TMCs, and TMCs-based heterostructure composites. It is obvious that introducing cations/anions to TMCs or constructing heterostructure can boost adsorption-catalytic capacity by regulating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 184 publications
0
2
0
Order By: Relevance
“…Moreover, the density of states of different materials was also calculated. The (CuCo)Se2 presents a higher density of states around the Fermi level in comparison to CoSe2 and (NiCo)Se2 (Figure 6a), meaning a better electron conductivity, which can help to accelerate the electrochemical reaction [8,47,48]. Charge density difference analyses are further displayed in Figure 6b,c, the yellow region stands for charge accumulation and the cyan region means charge depletion.…”
Section: Comparison Of Adsorption-catalytic Properties Of Bimetallic ...mentioning
confidence: 97%
See 2 more Smart Citations
“…Moreover, the density of states of different materials was also calculated. The (CuCo)Se2 presents a higher density of states around the Fermi level in comparison to CoSe2 and (NiCo)Se2 (Figure 6a), meaning a better electron conductivity, which can help to accelerate the electrochemical reaction [8,47,48]. Charge density difference analyses are further displayed in Figure 6b,c, the yellow region stands for charge accumulation and the cyan region means charge depletion.…”
Section: Comparison Of Adsorption-catalytic Properties Of Bimetallic ...mentioning
confidence: 97%
“…Currently, catalyst materials for Li-S batteries mainly include metal oxides, metal sulfides, metal nitrides, and metal phosphates with single metal components [8,9]. Considering the complex and multistep conversion of LiPSs in the process of charge-discharge and the difficulty of adjusting the electron structure of catalysts by single, it is extremely necessary to modify metal components for increasing active site and adjusting its catalytic activity with introduced metal ions [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heterostructures with more than one transition metal compound can more effectively endow the host material with optimal absorptivity and conductivity properties without requiring such trade-offs. 232 Constructing heterostructures with multiple metal cations can enable hosts that adsorb polysulfides effectively and also have high catalytic activity. Li et al have revealed that an effective heterostructure host can be produced by selecting two metal cations that produce compounds with large bandgap differences.…”
Section: Carbon Materials As Hostsmentioning
confidence: 99%
“…Heterostructures with more than one transition metal compound can more effectively endow the host material with optimal absorptivity and conductivity properties without requiring such trade-offs . Constructing heterostructures with multiple metal cations can enable hosts that adsorb polysulfides effectively and also have high catalytic activity.…”
Section: Lithium-sulfur Chemistrymentioning
confidence: 99%